Evaluating the impact of roof rainwater harvesting on hydrological connectivity and urban flood mitigation - Quang-Oai Lu; Reza Bahramloo; Jesús Rodrigo-Comino; Jun Wang; Ali Talebi; Quynh Thi Phuong Tran; Afshin Ghahramani; Mehdi Sepehri (Results in Engineering)
Urban flooding, particularly in arid and semi-arid regions, has become a growing concern in densely populated metropolitan areas. Roof rainwater harvesting is a form of low impact development that offers an effective solution for mitigating urban flooding, particularly in densely populated metropolitan areas. However, few scientific studies have attempted to model this dynamic, allowing us to increase water collection and reduce the risk of floods, especially in arid and semiarid areas. This study examined the impact of Roof rainwater harvesting on flood severity using the Borselli index of connectivity, which quantifies the degree to runoff connectivity between upstream and downstream areas, reflecting the potential for runoff to contribute to flooding. As a case study, we selected Hamadan, one of the world's oldest cities. The methodology involved quantifying HC under two scenarios: with and without Roof rainwater harvesting implementation. The results demonstrated a substantial reduction in hydrological connectivity when Roof rainwater harvesting was implemented, highlighting the valuable effectiveness of Roof rainwater harvesting. In contrast, without Roof rainwater harvesting, most of the areas, particularly in the middle and northern regions, had a high degree of hydrological connectivity. Overall, with the incorporation of RRWH, there was a significant shift toward increased connectivity. The areas characterized by very high and high degrees of hydrological connectivity in the absence of Roof rainwater harvesting decreased to 11.4 % and 20.4 %, respectively. Conversely, the moderate, low, and very low hydrological connectivity categories experienced increases of 27.9, 28.4, and 11.7 %, respectively. We conclude that this new evaluation of hydrological connectivity can serve as a valuable tool for assessing hydrological connectivity in urban areas and reveal to land managers where Roof rainwater harvesting is not effectively applied and where possible improvements must be made. However, the success of Roof rainwater harvesting in urban areas depends on technical, social, and regulatory support, as well as public acceptance for non-potable uses.